Implementasi Kebijakan Alih Fungsi Lahan di Kabupaten Kediri (Studi tentang alih fungsi lahan Kediri Waterpark di Desa Pagung, Kecamatan Semen, Kabupaten Kediri Berdasarkan Rencana Tata Ruang Wilayah Kabupaten Kediri Tahun 2010-2030) - Ella Yulisa Putri (Jurnal Administrasi Publik, 2015)
Abstract: The Implementation of land conversion Policy in Kabupaten Kediri (A Study of land function shift Kediri Waterpark Pagung, Kecamatan Semen, Kabupaten Kediri Based on Region Layout Plan Policy of Kabupaten Kediri 2010-2030). Increased land conversion due to increasing human needs for non agriculture land occurred in Kabupaten Kediri precisely in the Desa Pagung, Kecamatan Semen, Kabupaten Kediri as an artificial touristic Kediri Waterpark occurred in 2010. The land that was originally an agricultural land, now changed into tourism land. With the occurrence of the land conversion, the government of Kabupaten Kediri arrange local regulations number 14/2011 on Region Layout Plan of Kabupaten Kediri 2010-2030 to regulate land use and control of land conversion. The result of the research shows that the implementation of land conversion policy in Desa Pagung as an artificial touristic Kediri Waterpark which includes some stakeholders as the implementer is apporociate with the space use direction as written in the document of Region Layout Plan Policy of Kabupaten Kediri and it has also been planned that facility development in Kecamatan Semen. Nevertheless, there are implementation constraints is the absence of written covenant between the investor party and the government of Desa Pagung, furthermore there was no endorsement from the people of Desa Pagung. Keywords: Region Layout Plan (RLP), Land corversion, Kediri Waterpark Abstrak: Implementasi Kebijakan Alih Fungsi Lahan di Kabupaten Kediri (Studi tentang alih fungsi lahan Kediri Waterpark di Desa Pagung, Kecamatan Semen, Kabupaten Kediri Berdasarkan Rencana Tata Ruang Wilayah Kabupaten Kediri 2010-2030). Peningkatan alih fungsi lahan yang disebabkan meningkatnya kebutuhan manusia terhadap lahan non pertanian di Kabupaten Kediri tepatnya di Desa Pagung, Kecamatan Semen, Kabupaten Kediri sebagai kawasan wisata Kediri Waterpark selama mulai tahun 2010. Lahan yang awalnya merupakan lahan pertanian kini berubah menjadi kawasan wisata. Kegiatan tersebut membuat Pemerintah Kabupaten Kediri memformulasikan peraturan Kabupaten Kediri tahun 2011 nomor 14 dengan isi aturan rencana tata ruang di wilayah Kabupaten Kediri. Penelitian ini memberikan hasil bahwa implementasi perubahan fungsi lahan di Desa Pagung untuk Kediri Waterpark yang melibatkan beberapa stakeholder di Kabupaten Kediri telah sesuai dengan arah pemanfaatan ruang pada aturan tahun 2011 nomor 14 Kabupaten Kediri yang telah direncanakan pada pengembangan fasilitas Kecamatan Semen. Meskipun demikian, implementasi tersebut terdapat kendala, yaitu tidak ada perjanjian tertulis antara pihak desa dan investor yang mengakibatkan tidak adanya dukungan dari masyarakat Desa Pagung. Kata Kunci: Rencana Tata Ruang Wilayah, Alih Fungsi Lahan, Kediri Waterpark